(untitled) (Journal of the College of Basic Education, 2022)
My Research in making up of the theater Fashion about the Secret of philosophical thought and about the meaning of Optical pictures Which shaped by the relationships of Optical Pictures which shaped by the relationships of element of the theatre show , which connects with each other . As wellas the extences of acting the shape of theater Fashion (control) on appearances of the actor in the Field of ailing Fashion covers the natural body of the actor and express the appearances and dimensions of the fashion lakes part outside emotional expression , For the actor in the play averts . The dramatic fashion accused important optical avenge with the rest of visual elements , That style of fashion design stir up beautiful feelings by using fashion forming that is suitable with the nature of designable treatments to other elements .